The status and prospects of educational research in the Philippines a view from the academe - Cortes, Josefina R.
The years ahead hold great challenge to educational research in the Philippines not only because of the growing complexity of the contexts in which the educational process is occurring, but in view of the need for valid and reliable knowledge about this process in diverse and unique situations and for various purposes, such as educational policymaking, educational planning, curriculum assessment and improving the quality of student learning. However, the response to this challenge will depend very much on the training or researchers.
Keywords: Education -- Research; Education -- Research -- Philippines